Beware: adult-onset and fast-progressing Charcot-Marie-Tooth disease chameleons. Issue 6 (27th May 2022) - Pipis, Menelaos; Doherty, Carolynne; Skorupinska, Mariola; Laura, Matilde; Rossor, Alexander; Reilly, Mary
Abstract : Differentiating between an acquired and genetic aetiology of peripheral neuropathy poses a challenge to the neurologist. Contributing factors to this include a lack of family history of neuropathy, a rapid progres- sion of the clinical syndrome and/or the presence of features that are considered atypical for inherited neuropathies such as non-length dependent weakness and denervation. We present 6 patients with genetically confirmed CMT (2 NEFH, 3 MME and 1 TFG), who presented in adulthood with a rapid course of disease progression. The mean age of symptom onset was 37.8yrs (range 33–49) and despite an average disease duration of only 12.8yrs (range 7–16), 50% of patients (3/6) required a wheelchair or stick for mobility. All patients developed significant proximal involvement early on in the course of their disease with half of them having persistent evidence of non-length dependent weakness and denervation. All sporadic cases had CSF examinations and investigations for inflammatory causes of neuropathy, 1 patient had 2 courses of IVIG and another was considered for a nerve biopsy prior to achieving a genetic diagnosis. Certain adult onset CMT subtypes may mimic acquired neuropathies and in order to avoid missing treatable causes, the pursuit of both diagnostic avenues is often necessary. m.pipis@ucl.ac.uk